(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Background : Hypertension is a major public health problem globally in both the developed and developing countries and it leads to cardiovascular diseases, stroke and kidney failure. The aim of this study was to identify the deficiency of management and to know the overall approach both by physician and cardiologist in daily routine OPD setting. Materials and methods : The patients’ mean age was 54.9±9.9years, 53.2% were male and 46.8% were female. In history taking important symptoms, family history and smoking history were poorly recorded (51.2%). Results : Of the hypertensive patients, 78.4% were well controlled (BP<140/90). Out of 80 patients, 44 patients needed combined treatment either at the beginning or during follow up. Hypertension preceded before the onset of many newly detected diabetic subjects in our series. About 70% did have LVH and notably ACS were noted in 7.5% cases. 8.3% were obese. TIA/Hypertensive encephalopathy/CVD were detected in 6.2% cases. CCR or eGFR measurement done in only <1% of subjects routinely when we noted renalinsufficiency in 14% and interestingly some were having erectile dysfunction. Conclusion : A significant number (20%) of patients discontinued their BP check. At OPD setting Framingham 10 year CVD risk evaluated in <1% cases only. Refractory or Secondary HTN is seen in only 2 cases. Chatt Maa Shi Hosp Med Coll J; Vol.18 (1); Jan 2019; Page 49-51